Trends in Multiphase Modeling and Simulation of Sprays. (December 2014) - Kolakaluri, Ravi; Subramaniam, Shankar; Panchagnula, Mahesh V.
The characteristic features of sprays pose unique challenges to multiphase flow methods that are used to model and simulate their behavior. This article reviews the principal modeling challenges posed by sprays, and discusses the capabilities of different modeling approaches by classifying them according to the basis for their statistical representation and the level of closure. The article goes on to provide guidelines for their comparative assessment and also a perspective on the outlook for spray modeling. Multiphase flow simulation approaches that are used for spray computations are classified according to scale, accuracy, computational cost and problem complexity. The requirements of a simulation method to be successfully used for spray computation are then discussed. The review concludes with a perspective on the outlook for spray simulation methods.